1996
DOI: 10.1002/(sici)1096-9861(19960108)364:2<324::aid-cne10>3.3.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Urotensin II in the central nervous system of the frog Rana ridibunda: immunohistochemical localization and biochemical characterization

Abstract: Urotensin II (UII) is traditionally regarded as a product of the neurosecretory cells in the caudal portion of the spinal cord of jawed fishes. A peptide related to UII has been recently isolated from the frog brain, thereby providing the first evidence that UII is also present in the central nervous system of a tetrapod. In the present study, we have investigated the distribution of UII-immunoreactive elements in the brain and spinal cord of the frog Rana ridibunda by immunofluorescence using an antiserum dir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
2

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(74 citation statements)
references
References 0 publications
4
68
0
2
Order By: Relevance
“…1). Unlike many other neuropeptides, UII is not found in hypothalamic neurons, but is almost exclusively produced in motoneurons of the frog brainstem and spinal cord (Chartrel et al, 1996). The identification of UII in the frog brain confirmed that 1) UII is produced in extra-urophysial nervous tissues and 2) urotensinergic systems exist in vertebrate phyla outside the fish lineage (Conlon et al, 1997;Conlon, 2008;Vaudry et al, 2010).…”
Section: B Discovery Of Urotensin II In Mammalsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). Unlike many other neuropeptides, UII is not found in hypothalamic neurons, but is almost exclusively produced in motoneurons of the frog brainstem and spinal cord (Chartrel et al, 1996). The identification of UII in the frog brain confirmed that 1) UII is produced in extra-urophysial nervous tissues and 2) urotensinergic systems exist in vertebrate phyla outside the fish lineage (Conlon et al, 1997;Conlon, 2008;Vaudry et al, 2010).…”
Section: B Discovery Of Urotensin II In Mammalsmentioning
confidence: 99%
“…Specifically, in the European green frog, UII immunoreactivity is found in neurons of the hypoglossal nucleus of the medulla oblongata, which controls tongue muscles, and in a subpopulation of motoneurons of the spinal cord, particularly abundant in the caudal region (Chartrel et al, 1996). In the brain of rodents, UII is primarily expressed in brainstem nuclei including the dorsal motor nucleus of the vagus, the hypoglossal nucleus, the trigeminal motor nucleus, the facial motor nucleus, the abducens nucleus, and the trigeminal motor nucleus (Coulouarn et al, 1999;Dun et al, 2001;Dubessy et al, 2008).…”
Section: F the Urotensin II And Urotensin Ii-related Peptide Genesmentioning
confidence: 99%
“…The highest levels of expression of the UII gene are found in the CNS, specifically in motor neurons (Chartrel et al 1998, Coulouarn et al 1998, 1999, Dun et al 2001, Pelletier et al 2002, Egginger et al 2006. However, the bulk of all research into the UII-ergic system has mainly focused on the peripheral effects as the receptor is expressed predominantly in the periphery, in the cardiorenal system (Tal et al 1995, Ames et al 1999, Matsushita et al 2001, Elshourbagy et al 2002.…”
Section: Uts2r5mentioning
confidence: 99%
“…http://jme.endocrinology-journals.org DOI: 10.1530/JME-13-0274 (Chartrel et al 1998, Coulouarn et al 1998, 1999, Dun et al 2001, Pelletier et al 2002, Egginger et al 2006. Notably, UII mRNA is detected early in the formation of the rat embryonic ventral neural tube, at a developmental stage coincident with the differentiation of motor neurons (Coulouarn et al 2001).…”
Section: Journal Of Molecular Endocrinologymentioning
confidence: 99%
“…Urotensin II (UII) is a neuropeptide that was initially isolated from urophysis extracts of several species of fish (Pearson et al, 1980), with a core structure that is conserved through mollusks to mammals (Conlon et al, 1996(Conlon et al, , 1997Chartrel et al, 1998;Coulouarn et al, 1998Coulouarn et al, , 1999. UII has potent vasoconstrictor activity in the periphery (Russell et al, 2001;Bohm and Pernow, 2002).…”
Section: Introductionmentioning
confidence: 99%